2012
DOI: 10.1097/hjh.0b013e328359aa1f
|View full text |Cite
|
Sign up to set email alerts
|

Does cigarette smoking exacerbate the effect of blood pressure on the risk of cardiovascular and all-cause mortality among hypertensive patients?

Abstract: Smoking not only significantly increased the risk of CVD and all-cause mortality among hypertensive groups, but the synergistic effect on the risk of CVD and all-cause mortality existed between cigarette smoking and blood pressure category. Therefore, apart from hypertension management, smoking cessation should be an essential component for preventing deaths related to smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(51 reference statements)
3
8
0
Order By: Relevance
“…A large cohort found that there existed a combined interaction on an additive scale between current smoking and high SBP (140 mmHg) for the risk of IHD in the female adult Chinese population [ 14 ]. The significant relationship between blood pressure and CVD mortality, and the joint effects of smoking and blood pressure observed in our study were in agreement with previous studies [ 15 , 16 ]. The effect size was also similar compared with previous studies on the Chinese population, but was lower than studies on Western populations, which could be due to different smoking exposure doses or the profiles of lipid levels [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A large cohort found that there existed a combined interaction on an additive scale between current smoking and high SBP (140 mmHg) for the risk of IHD in the female adult Chinese population [ 14 ]. The significant relationship between blood pressure and CVD mortality, and the joint effects of smoking and blood pressure observed in our study were in agreement with previous studies [ 15 , 16 ]. The effect size was also similar compared with previous studies on the Chinese population, but was lower than studies on Western populations, which could be due to different smoking exposure doses or the profiles of lipid levels [ 17 , 18 , 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…To evaluate the effect of different confounding factors, we used three models to assess the association between blood pressure and mortality from all-cause, CVD, ischemic heart disease (IHD), and stroke. Variables and covariates for inclusion in the models were based on several previous studies, as well as the authors’ interest [ 14 , 15 ]. In model one, we only adjusted ages at entry.…”
Section: Methodsmentioning
confidence: 99%
“…Smoking did however confer the greatest increase in risk for IHD-hospitalisation in our study (after antihypertensive and lipid-lowering medication use) and interestingly, results suggested the risk might be attenuated somewhat by the use of antihypertensive and/or lipid-lowering medications. Synergistic effects between smoking and hypertension in CVD incidence have been reported previously [21]. Normalisation of blood pressure through medication use in current smokers could therefore explain the drop in risk to non-significant levels in our study.…”
Section: Discussionsupporting
confidence: 78%
“…Carotid intima-media thickness (CIMT) measured by ultrasound is widely used as a valid noninvasive measurement for subclinical atherosclerotic diseases, and is linked to the presence, extent, and development of atherosclerosis[21][24]_ENREF_18. Few studies have examined whether the association of age and metabolic syndrome with CIMT is modified by the status of cigarette smoking[13]. In the current study, we tested the hypothesis that cigarette smoking exacerbates the effects of age and metabolic syndrome on CIMT in a community-based sample of young adults from the Bogalusa Heart Study.…”
Section: Introductionmentioning
confidence: 98%